Cash Management Reform in Indonesia : Making the State Money Work Harder - Indonesian Ministry of Finance (Jakarta, 2014)
During the last decade, a body of common practices has emerged among developing countries on the legal, institutional and procedural foundations to support efficient cash management. These common practices have been reviewed and documented in guidance notes and publications on international practices issued by multilateral institutions like the International Monetary Fund (IMF), the World Bank (WB), and the Organization for Economic Co-operation and Development (OECD). Additionally, frequent peer-to-peer exchanges of experiences between countries have resulted in the continued evolution of cashmanagement practices to leverage improvements in data management, ICT and banking systems. The first part of this chapter examines international practices with regard to setting the objectives, as well as the legislative and institutional arrangements for cash management. It details the objectives and principles of cash management, its links with policy issues, information technology needs, incentives and sanctions to promote implementation, and the sequencing of the reform. The second part of the chapter describes Indonesia s experience with setting the objectives and institutional arrangements related to cash management, and with sequencing of the cash management reform. The concluding part describes the remaining challenges and suggests the way forward.